Natal origin of the invasive biosecurity pest, brown marmorated stink bug (Halyomorpha halys: Penatomidae), determined by dual‐element stable isotope‐ratio mass spectrometry. Issue 4 (9th December 2019) - Holder, Peter W; Van Hale, Robert J; Frew, Russell; George, Sherly; Armstrong, Karen F
Abstract: BACKGROUND: Post‐border detection of a single brown marmorated stink bug (BMSB) in New Zealand warranted a biosecurity response, the nature of which would be influenced by its status as part of an established population or as a new arrival. Stable isotope analysis has the potential to determine natal origins, but is difficult to achieve for samples as small as a single insect. Here an analytical modification to measure small samples was successfully trialled as a means to supply evidence as to the local or exotic natal origin of the intercepted BMSB specimen. RESULTS: Sufficient analytical sensitivity was achieved using a modified isotope ratio mass spectrometry method, involving thermolysis and carbon monoxide cryofocusing, to enable the simultaneous analysis of δ 2 H and δ 18 O from wings of the post‐border BMSB sample. The values were much lower than those of the New Zealand green vegetable bug, used as a local reference. However, they fell within the range of those for BMSB of Northern Hemisphere origin intercepted at the New Zealand border over the same time period, specifically overlapping with the USA and Italy, but not China. CONCLUSION: The isotope signature of the post‐border detected BMSB suggested a significantly cooler climate than the North Island of New Zealand, indicating that it was a new arrival and did not represent an established population. © 2019 The Authors. Pest Management Science published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry. Abstract : Provenance determination of pest insects can improve biosecurity and pest‐management outcomes. Here, a brown marmorated stink bug incursion of unknown origin is investigated using δ 2 H and δ 18 O, enabled by a modified analytical method.